Essential-Theoretical basis of foreign exchange rate state policies. - Третякова, Олена Василівна; Харабара, Віолетта; Грешко, Роман Ігорович (My University, 2021)
A stable exchange rate is the key to sustainable economic development of Ukraine. If Ukrainian citizens and foreign investors can plan the price of the currency in advance, their financial decisions will be as effective and thoughtful as possible. Carrying out such a forecasted currency policy in the long run provides confidence in the state as a whole. As a result, we can expect increased investment in the economy, as well as the active use of the hryvnia as a means of payment and accumulation of cash reserves.
Keywords: monetary policy; National Bank of Ukraine; exchange; devaluation; revaluation